Research on the impact of green finance on carbon emissions from the perspectives of nonlinearity and spatial spillover - Ma, Yu; He, Weijie; Cui, Xinyuan; xu, Zilu (Frontiers in Environmental Science, 2025)
The integration of low-carbon concepts into financial products through green finance promotes sustainable development and contributes to achieving carbon neutrality by mitigating carbon emissions. However, existing literature has rarely examined the impact of green finance on carbon emissions from nonlinear and spatial spillover perspectives, with insufficient exploration of the underlying mechanisms. This study aims to fill this research gap by adopting a nonlinear perspective and innovatively combining it with spatial econometric models to investigate the pathways and mechanisms through which green finance influences carbon emissions. Using annual panel data from 2007 to 2019 across 30 Chinese provinces, this research examines the relationship between green finance development and carbon emissions. We find that the relationship between green finance and carbon emissions follows an inverted U-shaped curve, with cross-regional spillover effects. Regionally, central and western China demonstrate stronger carbon emission reduction spillover effects compared to eastern China. Through mechanism tests, the study verifies the inverted U-shaped impact of green finance on carbon emissions via energy structure adjustment and technological advancement, further analyzing greenwashing phenomena and examining the lagged effects of green finance on emission reduction. This research emphasizes the significance of green finance in curbing carbon emissions, highlights its crucial role in promoting technological innovation and optimizing energy consumption structures, and calls for enhanced interprovincial cooperation to amplify the overall spatial impact of emission reduction efforts.